Lesson Study as a Means to Change Secondary Preservice Physics Teachers' Practice in the Use of Multiple Representations in Teaching - Teresa Conceição; Mónica Baptista; João Pedro Ponte (MDPI AG, 2021)
Multiple representations, such as experimental data, schemas, tables, and graphs, are an essential resource in science teaching. However, their use in the classroom typically poses a challenge for preservice teachers. The aim of this research is to examine changes in the practices of a group of preservice teachers regarding the use of multiple representations in the teaching of kinetic energy to 9th grade students, when this training is included in their initial teacher education program. For this purpose, a collaborative, reflexive, and student-learning centered approach, namely, a lesson study with three cycles, was implemented. A descriptive and content analysis for qualitative data collected showed improvement in the practices of the preservice teachers, namely on the representations both of the event that represents the "real" world, as well as of the scientific concepts. The results obtained contribute to deepening the knowledge on the use of multiple representations by preservice teachers, as well as to increasing the knowledge on using lesson study to develop the ability to use multiple representations during initial teacher education.